Detecting heritable phenotypes without a model using fast permutation testing for heritability and set-tests - Regev Schweiger (Nature Portfolio, 2018)
Standard approaches for heritability and set testing in statistical genetics rely on parametric models that might not hold in reality and give inflated p-values. Here, the authors develop a fast method for permutation-based testing of marker sets and of heritability that does not suffer from model misspecification.